2022
DOI: 10.3389/fnsys.2022.884260
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Reduces Neurotrophic Factors and pERK and pAKT Expression in Urinary Bladder of Female Mice With Cyclophosphamide-Induced Cystitis

Abstract: Imatinib mesylate is a tyrosine kinase inhibitor that inhibits platelet-derived growth factor receptor (PDGFR)-α, -β, stem cell factor receptor (c-KIT), and BCR-ABL. PDGFRα is expressed in a subset of interstitial cells in the lamina propria (LP) and detrusor muscle of the urinary bladder. PDGFRα + interstitial cells may contribute to bladder dysfunction conditions such as interstitial cystitis/bladder pain syndrome (IC/BPS) or overactive bladder (OAB). We have previously demonstrated that imatinib prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…A recent preclinical study reported that blockade of VEGF/VEGFR-2 signaling in rat model of acute and chronic cyclophosphamide (CYP)-induced cystitis resulted in increased bladder capacity and voided volume 18 . Similarly, imatinib, a tyrosine kinase inhibitor that inhibits PDGFR-A, -B, and C-kit, alleviated the altered expression of such receptors in rat bladders with CYP-induced cystitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent preclinical study reported that blockade of VEGF/VEGFR-2 signaling in rat model of acute and chronic cyclophosphamide (CYP)-induced cystitis resulted in increased bladder capacity and voided volume 18 . Similarly, imatinib, a tyrosine kinase inhibitor that inhibits PDGFR-A, -B, and C-kit, alleviated the altered expression of such receptors in rat bladders with CYP-induced cystitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum was aliquoted and frozen at −20 °C until analysis. We determined NGF and BDNF, IL-6 and CXC (CXCL9, CXCL10) protein content in the urinary bladder of control, CYP, RVS and CYP+RVS treatment groups (N=8) using ELISAs (Promega, Madison, WI and R&D Systems, Minneapolis, MN) as previously described (18,19,31,32,48). According to the manufacturer, the NGF E-max or BDNF E-max immunoassay systems (Promega, Madison, WI) demonstrate very low cross-reactivity with structurally related growth factors.…”
Section: Measurement Of Urinary Bladder Ngf Bdnf Cxcl9 Cxcl10 Il-6 Ex...mentioning
confidence: 99%
“…In this paper, we describe our characterization of the SISE model including, bladder function with conscious, open outlet continuous cystometry and somatic sensitivity with von Frey filament testing. We have also examined corticosterone expression, and expression of inflammatory mediators including neurotrophic factor (NGF, BDNF) (18)(19)(20), chemokine (CXC) and interleukin-6 (IL-6) (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) expression in the urinary bladder. These initial results demonstrated that CYP alone, or RVS alone creates a change in the inflammatory environment of the urinary bladder and a systemic increase in corticosterone expression but does not result in a change in bladder function or somatic sensitivity until CYP is combined with RVS (CYP+RVS).…”
Section: Introductionmentioning
confidence: 99%